Money illusion in free-to-play games - Behailu Shiferaw Benti; Dominik Haß; Georg Stadtmann (European University Viadrina, Department of Business Administration and Economics, 2021)
Regularly, free-to-play games use their own virtual currency for in-game store purchases. We analyze the money illusion phenomenon by examining free-to-playgames and their virtual currency exchange rate policies. We find that above pari exchange rates and advertising bonus packs instead of price discounts lead to money illusion on the side of the customer. Based on our findings, we derive managerial and policy implications.
Keywords: D18; L88; M37; Z28; 330; Money illusion; free-to-play games; virtual currency exchange rate; price incentives; bonus pack versus price discount